Pengaruh Model Pembelajaran RICOSRE terhadap Keterampilan Socioscientific Decision Making Siswa: (The Effect of the RICOSRE Learning Model on Students' Socioscientific Decision-Making Skills) - Rahma Dianti, Putri; Hidayah, Hikmah; Rahayu Ajeng Agesti, Asih (BIODIK, 2025)
This study aims to determine the effect of the RICOSRE model on students' socioscientific decision-making skills. This type of research was quasi-experimental with a pretest posttest non-equivalent control group design. The sample of the study consisted of class X1 (RICOSRE), X5 (PBL) and X2 (Conventional). The instruments used are in the form of learning tools and question sheets describing socioscientific decision-making skills. Analysis of research data used analysis of covariance (ANCOVA) and further tests to see real differences from the effect of independent variables using the Least Significant Different (LSD) test or the Least Significant Difference Test (LSD). The results of the analysis show that there is an influence of the learning model on socioscientific decision-making skills with an Fcount of 132.31 with a significance level of 0.00 <0.05. The class with the RICOSRE learning model has the highest score increase of 97.36%. The RICOSRE learning model demonstrates a statistically significant difference compared to the PBL and conventional learning models. These findings indicate that the RICOSRE model is effective and can be recommended as an alternative problem-based learning approach to enhance students’ decision-making skills. Abstrak. Penelitian ini bertujuan untuk mengetahui pengaruh model RICOSRE terhadap keterampilan socioscientific decision making siswa. Jenis penelitian yang dilakukan adalah kuasi eksperimen dengan desain penelitian pretest posttest non-equivalent control group design.  Sampel dari penelitian terdiri dari kelas X1 (RICOSRE), X5 (PBL) dan X2 (Konvensional). Instrumen yang digunakan yaitu berupa perangkat pembelajaran dan lembar soal uraian keterampilan socioscientific decision making. Analisis data penelitian menggunakan analisis kovarian (ANCOVA) dan uji lanjut untuk melihat perbedaan nyata dari pengaruh variabel bebas menggunakan  uji Least Significant Different (LSD) atau Uji Beda Nyata Terkecil (BNT). Hasil analisis menunjukkan terdapat pengaruh model pembelajaran terhadap keterampilan socioscientific decision making dengan Fhitung sebesar 132,31 dengan taraf signifikansi sebesar 0,00 < 0,05. Kelas dengan model pembelajaran RICOSRE memiliki peningkatan nilai tertinggi yaitu sebesar 97,36%. Pembelajaran model RICOSRE berbeda nyata dengan model PBL dan konvensional.